Modeling and characterization of graphene for efficient millimeterwave and terahertz antennas - Gatte, Mohammed Taih author (School of Computer and Communication Engineering, 2017)
Figure 1.5 illustrates the overview of this dissertation. This study focuses on the calculation of the surface properties of a monolayer graphene according to the Kubo formula. Monolayer graphene is selected due to its conductivity, mechanical, chemical, and optical properties. Upon calculation of its surface impedance, these values are then integrated with Microwave studio CST. Besides, this study also concentrates on designing microstrip patch antenna operating in the MMW (64 GHz) and THz (1 THz, 1.29 THz and 1.49 THz) based on the modeled monolayer graphene (ND-G an D-G).